2023
DOI: 10.1021/acsomega.3c03735
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, Kinetics, and Isotherm Studies of Methyl Thioninium Chloride Removal from Simulated Solutions Using Chitosan Derivatives

Manar El-Sayed Abdel-Raouf,
Reem Kamal Farag,
Ahmed A. Farag
et al.

Abstract: Methylene blue (MB) dye or methyl thioninium chloride is one of the hazardous cationic dyes that are discharged into the textile effluent causing a highly negative environmental impact. The present work targets the investigation of the adsorption performance of some chitosan-modified products toward the MB dye from simulated solutions. The claimed chitosan derivatives were prepared, characterized, and applied for the removal of lead and copper cations from an aqueous medium in a previous work. These include: N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The q e1 and q e2 values indicate the equilibrium adsorption capacity of each adsorbent, with Fr-fMWCNT-Fe 3 O 4 showing a higher value than Fr-fMWCNT for both models (Figure a,b). These results are consistent with earlier research , which have shown that the incorporation of metal oxides onto carbon nanotubes can enhance their adsorption performance for various dyes and pollutants, including CV. Finally, the findings demonstrate that Fr-fMWCNT-Fe 3 O 4 has a higher adsorption capacity and faster adsorption kinetics for CV than Fr-fMWCNT.…”
Section: Resultsmentioning
confidence: 99%
“…The q e1 and q e2 values indicate the equilibrium adsorption capacity of each adsorbent, with Fr-fMWCNT-Fe 3 O 4 showing a higher value than Fr-fMWCNT for both models (Figure a,b). These results are consistent with earlier research , which have shown that the incorporation of metal oxides onto carbon nanotubes can enhance their adsorption performance for various dyes and pollutants, including CV. Finally, the findings demonstrate that Fr-fMWCNT-Fe 3 O 4 has a higher adsorption capacity and faster adsorption kinetics for CV than Fr-fMWCNT.…”
Section: Resultsmentioning
confidence: 99%